#TITLE_ALTERNATIVE# - WIDYANTI (234 99 006), ARI
Intense interactions between man and computers are becoming more and more common in tha past decade and the years to come. When interacting with a computer, he or she experinece an amount of workload which are of physical and mental types. These workloads, when too much, may decrease operator's performance and potentially followed by reduction in the overall performance of the man and computer system. It is therefore of importance to study these workloads. This thesis focuses on mental workload in the HCl particularly in developing a model to predict the mental workload that may arise and to help find the solution. Literature shows that the contributing factors to the workload are: - mental demand - boredom - work environment - fatigue - task difficulty - temporal demand A questionnaire was designed to get the responden's validation to those factors. The chosen respondents are university students considering they are intense users of computers. The respondents are carefully selected regarding their colour literacy and maximum capacity of O2, since the model to be developed is based on tasks designed by Stroop. The response of the respondents are validated by several physiological criteria, that is: heart rate and work performance. The statistical test of the response shows that the mental workload is highly corelated with the heart rate. The resulting model of this research is proved to be able to quantify the magnitude of the human mental workload during the interaction with computer on two different Stroop task design with different degree of importance on each factors in accordance to the work environment.